Comparison of polarization switching in ferroelectric TGS and relaxor SBN crystals - Matyjasek, K.; Orłowski, M. (Condensed Matter Physics, 2013)
The comparative experimental analysis of polarization reversal kinetics in conventional homogeneous triglycine sulfate (NH₂ CH₂ COOH)₃ ˙ H₂SO₄; TGS) and relaxor strontium barium niobate (Sr₀.₆₁Ba₀.₃₉Nb₂O₆; SBN) crystals have been performed in a broad range of measurement conditions. The experimental data have been collected from microscopic observation of the domain structure, switching current and D-E hysteresis loop registration. The hysteresis loop and dielectric spectra has a strong link to the configuration of ferroelectric microdomains. The domain structure dynamics was examined by the nematic liquid crystal (NLC) method.